2021
DOI: 10.3389/fmicb.2021.736751
|View full text |Cite
|
Sign up to set email alerts
|

Niche Differentiation of Arsenic-Transforming Microbial Groups in the Rice Rhizosphere Compartments as Impacted by Water Management and Soil-Arsenic Concentrations

Abstract: Arsenic (As) bioavailability in the rice rhizosphere is influenced by many microbial interactions, particularly by metal-transforming functional groups at the root-soil interface. This study was conducted to examine As-transforming microbes and As-speciation in the rice rhizosphere compartments, in response to two different water management practices (continuous and intermittently flooded), established on fields with high to low soil-As concentration. Microbial functional gene composition in the rhizosphere an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Comparing the relative abundance of soil microbes, it has been observed that bacteria are the dominant group over archaea and fungi existing in the rhizosphere soil that surrounds plant roots, whereas among the bacterial phyla, Proteobacteria is the predominant phylum found in most paddy rhizosphere soils ( Somenahally et al, 2021 ; Zhang et al, 2021 ). China-based research studies have demonstrated that the most abundant bacterial genera affiliated with the core microbial communities of rice rhizosphere soils under standard crop management are Anaeromyxobacter , Arenimonas , Arthrobacter , Bacillus , Bellilinea , and 15 other bacterial genera, all of which are well-known to share in the overall growth and health of rice plants ( Zhou et al, 2020 ; Sahu et al, 2022 ).…”
Section: Toward Eco-efficient N Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the relative abundance of soil microbes, it has been observed that bacteria are the dominant group over archaea and fungi existing in the rhizosphere soil that surrounds plant roots, whereas among the bacterial phyla, Proteobacteria is the predominant phylum found in most paddy rhizosphere soils ( Somenahally et al, 2021 ; Zhang et al, 2021 ). China-based research studies have demonstrated that the most abundant bacterial genera affiliated with the core microbial communities of rice rhizosphere soils under standard crop management are Anaeromyxobacter , Arenimonas , Arthrobacter , Bacillus , Bellilinea , and 15 other bacterial genera, all of which are well-known to share in the overall growth and health of rice plants ( Zhou et al, 2020 ; Sahu et al, 2022 ).…”
Section: Toward Eco-efficient N Managementmentioning
confidence: 99%
“…Comparing the relative abundance of soil microbes, it has been observed that bacteria are the dominant group over archaea and fungi existing in the rhizosphere soil that surrounds plant roots, whereas among the bacterial phyla, Proteobacteria is the predominant phylum found in most paddy rhizosphere soils (Somenahally et al, 2021;Zhang et al, 2021).…”
Section: Role Of Microbial Communities In Rice Soilsmentioning
confidence: 99%